Big five personality, transformational leadership, psychological safety, and employee engagement of private sector employees in Southern Thailand - Norsiah Mat; Parichat Jansriboot; Norazuwa Mat (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines the relationship between five factor model of personality (i.e, extraversion, conscientiousness, openness to experience, agreeableness and neuroticism), transformational leadership and psychological safety and their impact on employee engagement. A total of 402 of private sector companies in Southern Thailand participated in this study. PLS-SEM was used to analyze the data. Overall measurement model showed appropriate psychometric properties in term of reliability and validity. The propose model of this research has relied primarily on reflective measurement model. Out of the five personality factors, three proved to have an influence on employee engagement (extraversion, conscientiousness, and openness to experience), however the influence of agreeableness and neuroticism were not supported. Transformational leadership and psychological safety also showed direct influence on employee engagement. The results of predictive power of the structural model was 0.337 indicating that 33.7% of the variance in the employee engagement construct was explained by the five factor model of personality, transformational leadership and psychological safety. Theoretical and practical implications of the study are highlighted. Finally, limitations and further research are discussed.